2010
DOI: 10.1016/j.mod.2009.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Sonic hedgehog is involved in formation of the ventral optic cup by limiting Bmp4 expression to the dorsal domain

Abstract: Accumulating evidence suggests that Sonic hedgehog (Shh) signaling plays a crucial role in eye vesicle patterning in vertebrates. Shh promotes expression of Pax2 in the optic stalk and represses expression of Pax6 in the optic cup. Shh signaling contributes to establishment of both proximal-distal and dorsal-ventral axes by activating Vax1, Vax2, and Pax2. In the dorsal part of the developing retina, Bmp4 is expressed and antagonizes the ventralizing effects of Shh signaling through the activation of Tbx5 expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 55 publications
5
44
0
Order By: Relevance
“…In common with other mouse models of HPE (Allen et al 2007;Cole and Krauss 2003;Martinelli and Fan 2007;Seppala et al 2007;Tenzen et al 2006;Zhang et al 2011;Zhang et al 2006) Vax1 mutants have reduced Shh signaling in the early craniofacial midline, consistent with a downsteam role previously identified in other developmental contexts (Hallonet et al 1999;Kim and Lemke 2006;Take-uchi et al 2003;Zhao et al 2010). …”
Section: Vax1supporting
confidence: 85%
See 1 more Smart Citation
“…In common with other mouse models of HPE (Allen et al 2007;Cole and Krauss 2003;Martinelli and Fan 2007;Seppala et al 2007;Tenzen et al 2006;Zhang et al 2011;Zhang et al 2006) Vax1 mutants have reduced Shh signaling in the early craniofacial midline, consistent with a downsteam role previously identified in other developmental contexts (Hallonet et al 1999;Kim and Lemke 2006;Take-uchi et al 2003;Zhao et al 2010). …”
Section: Vax1supporting
confidence: 85%
“…The aetiological basis of these disorders is complex but reflects a failure of normal facial development mediated through genetic and environmental factors (Dixon et al 2011). A number of independent studies have found associations between the homeobox gene VAX1 and CLP in human populations (Butali et al 2013;de Aquino et al 2013;de Araujo et al 2016;Gowans et al 2016;Peng et al 2016;Slavotinek et al 2012;Wang et al 2016;Wen and Lu 2016;Zawislak et al 2014) and Vax genes act downstream of Sonic hedgehog (Shh) (Hallonet et al 1999;Kim and Lemke 2006;Take-uchi et al 2003;Zhao et al 2010) and as both Fgf and Wnt antagonists in a number of developmental contexts (Bharti et al 2011;Vacik et al 2011). Vax1 is first expressed in the early central nervous system (CNS) (Bertuzzi et al 1999;Hallonet et al 1998;Taglialatela et al 2004) and targeted disruption in mice produces multiple defects in the visual apparatus, including coloboma and absence of the optic chiasma, accompanying growth defects in the medioventral CNS, altered axonal guidance and duplication of the pituitary gland (Bertuzzi et al 1999;Bharti et al 2011;Hallonet et al 1999;Taglialatela et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…S2A-C). Previously, in a study of the optic cup of Smoothened (Smo, a mediator of Shh signaling) conditional knockout mice, Vax2 expression was found to be downregulated (Zhao et al, 2010). However, in the optic cup of Gli (a transcription factor in the Shh pathway) mutant mice, Vax2 expression was not changed (Furimsky and Wallace, 2006).…”
Section: Bmp Signaling Directly Regulates D-v Polarization and Invagimentioning
confidence: 99%
“…Previous studies have suggested that bone morphogenetic protein (BMP) and Sonic hedgehog (Shh) are candidates for the upstream signal of Tbx5 and Vax2 within the context of D-V polarization (reviewed by Yang, 2004;Zhao et al, 2010;Kobayashi et al, 2010). In early mouse optic vesicles, Bmp4 is expressed on the distal portion and subsequently confined to the dorsal portion (Furuta and Hogan, 1998;Behesti et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A long-standing program of research in the Lemke laboratory concerns the patterning of the vertebrate eye (Kim (Huh et al 1999;Halilagic et al 2007;Veien et al 2008;Zhao et al 2010). Shh induces the transcription factor Vax2 (Kim and Lemke 2006), previously found to be expressed in the ventral retina and to regulate D/V eye patterning (Barbieri et al 1999;Kim and Lemke 2006).…”
Section: The Role Of Vax Genes In Generating Dominant-negative Tcf7l2mentioning
confidence: 99%